Comprehensive cardiac assessment with multislice computed tomography: evaluation of left ventricular function and perfusion in addition to coronary anatomy in patients with previous myocardial infarction. Issue 12 (1st June 2006) - Henneman, M M; Schuijf, J D; Jukema, J W; Lamb, H J; de Roos, A; Dibbets, P; Stokkel, M P; van der Wall, E E; Bax, J J
Abstract : Objective: To evaluate a comprehensive multislice computed tomography (MSCT) protocol in patients with previous infarction, including assessment of coronary artery stenoses, left ventricular (LV) function and perfusion. Patients and methods: 16-slice MSCT was performed in 21 patients with previous infarction; from the MSCT data, coronary artery stenoses, (regional and global) LV function and perfusion were assessed. Invasive coronary angiography and gated single-photon emission computed tomography (SPECT) served as the reference standards for coronary artery stenoses and LV function/perfusion, respectively. Results: 236 of 241 (98%) coronary artery segments were interpretable on MSCT. The sensitivity and specificity for detection of stenoses were 91% and 97%. Pearson's correlation showed excellent agreement for assessment of LV ejection fraction between MSCT and SPECT (49 (13)% v 53 (12)%, respectively, r  =  0.85). Agreement for assessment of regional wall motion was excellent (92%, κ  =  0.77). In 68 of 73 (93%) segments, MSCT correctly identified a perfusion defect as compared with SPECT, whereas the absence of perfusion defects was correctly detected in 277 of 284 (98%) segments. Conclusions: MSCT permits accurate, non-invasive assessment of coronary artery stenoses, LV function and perfusion in patients with previous infarction. All parameters can be assessed from a single dataset.